2015
DOI: 10.3382/ps/pev164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two catching methods on the occurrence of lesions in broilers

Abstract: During the catching of broilers for slaughter, 2 to 3 birds are grabbed per hand at one leg at the same time. From an animal welfare point of view, this procedure is under critical observation from animal welfare administration and the general public.In this paper 2 catching methods were compared: the routinely used 1-leg catching method, and a second tech-nique whereby birds were grabbed by both legs with a maximum of 2 birds per hand (2-leg catching method). Lesions on the body, legs, and wings (hemorrhages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
5
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 14 publications
5
35
5
4
Order By: Relevance
“…In containers with a lid and in those that require a drawer to slide into a module, there is a risk of birds getting trapped and injured. In Germany, after birds had been caught and carried by one leg for 5 m and then loaded into modules with drawers, for light birds (1.9 kg) and for heavy birds (2.5 kg), the % of the flock with leg damage was 0.26% and 0.47% respectively, and with wing damage it was 5.83% and 12.26%, respectively (Langkabel et al 2015).…”
Section: Catching and Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…In containers with a lid and in those that require a drawer to slide into a module, there is a risk of birds getting trapped and injured. In Germany, after birds had been caught and carried by one leg for 5 m and then loaded into modules with drawers, for light birds (1.9 kg) and for heavy birds (2.5 kg), the % of the flock with leg damage was 0.26% and 0.47% respectively, and with wing damage it was 5.83% and 12.26%, respectively (Langkabel et al 2015).…”
Section: Catching and Handlingmentioning
confidence: 99%
“…Liver rupture was found in 6.1% of DOAs and muscle injury in 1.5% F o r R e v i e w O n l y (Kittelsen et al 2015a). Variation between catching teams can affect % DOA (Nijdam et al 2004) and the % of birds with bruised wings or breasts (Taylor and Helbacka 1968;Langkabel et al 2015).…”
Section: Catching and Handlingmentioning
confidence: 99%
“…In this study, there was no evidence that problems associated with inappropriate handling increased the risk of mortality. As variation has been reported between catching teams in the risk of broiler mortality and injury (Taylor and Helbacka 1968;Nijdam et al 2004;Langkabel et al 2015), this suggests that the catching team observed handled the birds in a competent manner. When loading was undertaken efficiently, and the speed of loading was high, the loading was undertaken quicker, and the risk of mortality was lower.…”
Section: Discussionmentioning
confidence: 84%
“…Catching and carrying a broiler inverted by its legs can cause wing flapping and struggling (Newberry and Blair 1993) and sometimes injury and death (Gregory and Austin 1992;Nijdam et al 2006). Variation between the manner in which different catching teams handle the birds can affect DOA % (Nijdam et al 2004) and the percentage of birds with bruising (Taylor and Helbacka 1968;Langkabel et al 2015;Jacobs et al 2017). Bruising is a superficial injury that occurs after trauma (Hamdy et al 1961).…”
Section: Introductionmentioning
confidence: 99%
“…As fraturas podem ser ocasionadas durante a apanha, engradamento das aves, transporte, espera e retirada das aves das caixas de transporte (WELFARE QUALITY, 2009). E pode sofrer influência do método de apanha, dos funcionários encarregados da apanha, do peso das aves e do método de abate (LANGKABEL et al, 2015;KITTELSEN et al, 2015b).…”
Section: Principais Lesões Causadas Pelo Manejo Inadequado Em Frango unclassified